Análisis jurídico del delito de contrabando y el desequilibrio económico del Ecuador. - Ramírez Hurtado, Kevin Alexander (2023)
Smuggling is a crime, which has become both a social, economic and legal problem, as well as an informal economic activity, causing millionaire losses in Ecuador since it caused a high rate of unemployment in Ecuadorian people who work for national companies and for the state a great loss of tax evasion, that is why a number of proposed guidelines are put forward to help control smuggling but not eradicate it, due to, in order make it happen, first of all, unemployment, corruption and poverty must be ended. The purpose of this research was to conduct a doctrinal and legal study on the crime of smuggling and economic imbalance in Ecuador. This study had a qualitative approach to analyze and compare information from similar works; similarly, it has an experimental design and a descriptive scope, where the following methods were used; deductive, inductive, analytical-synthetic, scientific and statistical method, to finally obtain final results by applying two techniques such as the survey and interview to reference the crime of smuggling and economic imbalance, where different proposed guidelines are proposed in reference to the World Customs Organization, since they are useful strategies for the control of smuggling, concluding that smuggling is a social phenomenon that has existed since ancient times that affects the economic imbalance of the country, because many citizens see it as a source of work and not as a crime, for this reason, it cannot be eradicated, but a legal proposal for its control should be carried out.